The homemade god : a novel - Joyce, Rachel (The Dial Press, 2025)
"There is a heatwave across Europe, and four siblings have gathered at their family's lake house to seek answers about their father, a famous artist, who recently remarried a much younger woman and decamped to Italy to finish his long-awaited masterpiece. Now he is dead. And there is no sign of his final painting. As the siblings try to piece together what happened, they spend the summer in a state of lawlessness: living under the same roof for the first time in decades, forced to confront the buried wounds they incurred as his children, and waiting for answers. Though they have always been close, the things they learn that summer--about themselves, and their father--will drive them apart before they can truly understand his legacy. Meanwhile, their stepmother's enigmatic presence looms over the house. Is she the force that will finally destroy the family for good?"--